Carbon nitride nanotube photocatalyst, preparation method thereof and application of carbon nitride nanotube photocatalyst in photocatalysis of copper oxide

Through the treatment of acid solution reconstruction and cyanamide solution, a carbon nitride nanotube photocatalyst with excellent morphology was prepared, which solved the problem of body phase defects of the existing carbon nitride photocatalysts and significantly improved its photocatalytic performance and practical application potential.

CN119503740APending Publication Date: 2025-02-25JIANGSU UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411634038.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing carbon nitride photocatalysts have bulk phase defects, such as low specific surface area, few reactive sites, high photocarrier recombination rate and weak visible light absorption efficiency, which limits its photocatalytic performance and practical application.

Method used

The morphology of melamine-melamine supramolecular aggregates is controlled through the reconstruction orientation of the acid solution, and the cyanamine solution is added during the calcination process to maintain the tubular morphology and is not prone to collapse, thereby preparing a hollow tubular nanocarbon nitride material with good morphology.

Benefits of technology

The specific surface area and active sites of the carbon nitride nanotube photocatalyst are improved, the absorption utilization rate of visible light is enhanced, and its performance in photocatalytic copper oxide reaction is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503740A_ABST
    Figure CN119503740A_ABST
Patent Text Reader

Abstract

The invention provides a carbon nitride nanotube photocatalyst as well as a preparation method and application thereof in photocatalysis of copper oxide, and belongs to the technical field of photocatalytic materials. The preparation method comprises the following steps: firstly, mixing melamine and cyanuric acid in an organic solvent, reacting at normal temperature to obtain a melamine-cyanuric acid spherical supramolecular aggregate, then putting the supramolecular aggregate into an acid solution to reconstruct and grow into a rod-like precursor, then treating the rod-like precursor with a cyanamide solution to obtain a supramolecular precursor, and finally preparing the melamine-cyanuric acid spherical supramolecular aggregate. And carrying out high-temperature calcination on the supramolecular precursor to obtain the carbon nitride nanotube photocatalyst. Compared with a common carbon nitride catalyst, the prepared carbon nitride nanotube photocatalyst has a larger specific surface area, active sites are increased, and the absorption and utilization rate of visible light is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photocatalytic materials, and in particular to a carbon nitride nanotube photocatalyst and a preparation method thereof and application thereof in photocatalytic copper oxidation. Background Art

[0002] At present, the more common methods for recovering metals in industry are pyrometallurgy and hydrometallurgy. Although the above methods can recover metals, they have defects to varying degrees. For example, the high-temperature operation in the pyrometallurgical process will produce a lot of air pollution, seriously affect the environment, consume a lot of energy, increase production costs, and the operation process is complicated. It has high requirements for equipment and technology, and is difficult to operate. The production capacity of hydrometallurgy is relatively low, and the reaction rate is slow, resulting in low overall production efficiency. In the hydrometallurgical process, the equipment is easily corroded and the maintenance cost is high. The hydrometallurgical process is long, and liquid-solid separation is difficult, which increases the operation time and cost. It can be seen that the existing commonly used methods for recovering metals generally have problems such as huge energy consumption, serious secondary pollution to the environment, and difficulty in operation.

[0003] Compared with traditional chemical methods for recovering metals, photocatalytic technology uses light energy as energy. Compared with traditional methods, it has lower energy consumption and has the advantages of mild reaction, no pollution, and sustainable development. Carbon nitride, as a polymer semiconductor photocatalyst, has the advantages of low price, high stability and safety, and visible light response. The conventional technology for preparing carbon nitride photocatalysts is thermal polymerization. The preparation process is simple and convenient. Nitrogen-carbon polymers are synthesized by thermal polymerization of precursors rich in carbon and nitrogen elements. However, there are a large number of bulk defects in the graphite phase carbon nitride obtained by this technology, such as low specific surface area, few reactive active sites, high photocarrier recombination rate, and weak visible light absorption efficiency. These problems greatly limit the photocatalytic performance of carbon nitride photocatalysts, thereby limiting their practical applications.

[0004] By regulating the morphology of carbon nitride materials, such as hollow structures, and taking advantage of their low density and large specific surface area, the photocatalytic performance of carbon nitride photocatalysts can be optimized and improved. Therefore, studying the controllable preparation method of tubular carbon nitride photocatalysts is of great significance for improving the practical application of carbon nitride photocatalysts. Summary of the invention

[0005] In view of this, the present invention provides a carbon nitride nanotube photocatalyst and a preparation method thereof and application in photocatalytic copper oxidation. The present invention controls the morphology of melamine-cyanuric acid supramolecular aggregates through reconstruction guidance of an acidic solution, and by adding a cyanamide solution, the supramolecular precursor maintains a tubular morphology and is not easy to collapse during the calcination process, thereby obtaining a hollow tubular nano carbon nitride material with good morphology.

[0006] The first object of the present invention is to provide a method for preparing a carbon nitride nanotube photocatalyst, comprising the following steps:

[0007] (1) placing melamine and cyanuric acid in an organic solvent, stirring and reacting at room temperature, and centrifuging, washing, and drying in sequence after the reaction to obtain melamine-cyanuric acid spherical supramolecular aggregates;

[0008] (2) placing the obtained spherical supramolecular aggregates in an acidic solution for heating reaction, and after the reaction is completed, centrifuging, washing, and drying in sequence to obtain a rod-shaped precursor;

[0009] (3) placing the rod-shaped precursor in a cyanamide solution and reacting it at room temperature, and after the reaction is completed, centrifuging and drying are performed in sequence to obtain a supramolecular precursor;

[0010] (4) calcining the supramolecular precursor at high temperature to obtain carbon nitride nanotube photocatalyst.

[0011] Furthermore, in step (1), the mass ratio of melamine to cyanuric acid is 1-1.5:1-1.5.

[0012] Furthermore, the organic solvent in step (1) is selected from any one of dimethyl sulfoxide and ethylene glycol.

[0013] Furthermore, in step (2), the pH value of the acidic solution is controlled within the range of 2-3, the heating reaction temperature is 70-80° C., and the heating reaction time is 4-6 hours.

[0014] Furthermore, in step (2), the ratio of the spherical supramolecular aggregates to the acidic solution is (2-3) g: (100-150) mL.

[0015] Furthermore, the concentration of the cyanamide solution in step (3) is 5-20%, and the ratio of the rod-shaped precursor to the cyanamide solution is (1-1.5) g: (20-30) mL.

[0016] Furthermore, the calcination in step (4) is carried out in a nitrogen tube furnace.

[0017] Furthermore, the heating rate in the nitrogen tubular furnace is 2-4°C / min, the calcination temperature is 500-600°C, and the calcination time is 4-6 hours.

[0018] The second object of the present invention is to provide a carbon nitride nanotube photocatalyst prepared according to the method.

[0019] The third object of the present invention is to provide an application of the carbon nitride nanotube photocatalyst in a photocatalytic oxidation copper dissolution reaction.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1. Compared with carbon nitride prepared by traditional methods, the carbon nitride nanotube photocatalyst prepared by the present invention has a larger specific surface area, more active sites, and enhanced absorption and utilization rate of visible light.

[0022] 2. The carbon nitride nanotube photocatalyst prepared by the present invention is suitable for photocatalytic oxidation copper dissolution reaction. Compared with the traditional catalyst titanium dioxide (commercial code P25), it has better visible light response characteristics and has great application potential in dissolving and recovering copper using photocatalytic technology.

[0023] 3. The preparation method of the carbon nitride nanotube photocatalyst provided by the present invention is easy to control, low in cost, and is conducive to mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 This is the X-ray diffraction spectrum of the carbon nanotube nitride photocatalyst prepared in Example 1 of the present invention, wherein the abscissa represents the 2θ angle and the ordinate represents the intensity.

[0025] Figure 2 This is the Fourier transform infrared spectrum of the carbon nanotube photocatalyst prepared in Example 1 of the present invention, wherein the abscissa represents the wave number and the ordinate represents the transmittance.

[0026] Figure 3 is a scanning electron microscope image of Example 1 of the present invention and Comparative Example 1; wherein, Figure 3 a is a scanning electron micrograph of the spherical supramolecular aggregates of melamine-cyanuric acid prepared in Example 1 of the present invention; Figure 3 b is a scanning electron microscope image of the rod-shaped precursor obtained in Example 1 of the present invention; Figure 3 c is a scanning electron microscope image of the carbon nitride nanotube photocatalyst prepared in Example 1 of the present invention; Figure 3 d is a scanning electron microscope image of the carbon nitride photocatalyst obtained in Comparative Example 1 of the present invention.

[0027] Figure 4 is a scanning electron microscope image of Examples 2-4 of the present invention and Comparative Example 2; wherein, Figure 4 a is a scanning electron micrograph of the spherical supramolecular aggregates of melamine-cyanuric acid obtained in Example 2 of the present invention; Figure 4 b is a scanning electron microscope image of the rod-shaped precursor obtained in Example 3 of the present invention; Figure 4 c is a scanning electron microscope image of the carbon nitride nanotube photocatalyst obtained in Example 4 of the present invention; Figure 4 d is a scanning electron microscope image of the carbon nitride photocatalyst obtained in Comparative Example 2 of the present invention.

[0028] Figure 5This is a solid ultraviolet-visible diffuse reflectance spectrum of the carbon nitride nanotube photocatalyst prepared in Example 1 of the present invention.

[0029] Figure 6 This is a copper foil dissolution rate curve of the carbon nitride nanotube photocatalyst prepared in Example 1 of the present invention in the photocatalytic copper oxidation reaction under full spectrum conditions.

[0030] Figure 7 This is a comparison chart of the photocatalytic copper oxidation effects of the carbon nitride nanotube photocatalyst prepared in Example 1 and the commercial TiO2 photocatalyst under visible light conditions. DETAILED DESCRIPTION

[0031] In some embodiments, the present invention provides a method for preparing a carbon nitride nanotube photocatalyst, comprising the following steps:

[0032] (1) placing melamine and cyanuric acid in an organic solvent, stirring and reacting at room temperature, and centrifuging, washing, and drying in sequence after the reaction to obtain melamine-cyanuric acid spherical supramolecular aggregates;

[0033] (2) placing the obtained spherical supramolecular aggregates in an acidic solution for heating reaction, and after the reaction is completed, centrifuging, washing, and drying in sequence to obtain a rod-shaped precursor;

[0034] (3) placing the rod-shaped precursor in a cyanamide solution and reacting it at room temperature, and after the reaction is completed, centrifuging and drying are performed in sequence to obtain a supramolecular precursor;

[0035] (4) calcining the supramolecular precursor at high temperature to obtain carbon nitride nanotube photocatalyst.

[0036] In some embodiments, the mass ratio of melamine to cyanuric acid in step (1) is 1-1.5:1-1.5 , Preferably it is 1-1.5:1, more preferably 1:1.

[0037] In some embodiments, the organic solvent in step (1) is selected from any one of dimethyl sulfoxide and ethylene glycol. Melamine and cyanuric acid can effectively form aggregates in an organic solvent, wherein cyanuric acid has the effect of improving the hydrophilicity of the surface of the spherical supramolecular aggregates.

[0038] In some embodiments, the pH value of the acidic solution in step (2) is controlled within the range of 2-3, and the acidic solution is any one of a hydrochloric acid solution and a sulfuric acid solution. The change in the ionization equilibrium in the acidic solution enhances the intermolecular forces, which is conducive to the growth of the rod-shaped precursor.

[0039] In some embodiments, the heating reaction temperature in step (2) is 70-80°C, preferably 80°C, and the heating reaction time is 4-6 hours, preferably 6 hours.

[0040] In some embodiments, the ratio of the spherical supramolecular aggregates to the acidic solution in step (2) is (2-3) g:(100-150) mL, preferably (2-3) g:100 mL, and more preferably 2 g:100 mL.

[0041] In some embodiments, the concentration of the cyanamide solution in step (3) is 5-20%, and the ratio of the rod-shaped precursor to the cyanamide solution is (1-1.5) g: (20-30) mL, preferably (1-1.5) g: 30 mL, and more preferably 1.5 g: 30 mL.

[0042] In some embodiments, the calcination in step (4) is performed in a nitrogen tube furnace. The nitrogen atmosphere helps maintain the morphology of the supramolecular precursor during the calcination process.

[0043] In some embodiments, the heating rate in the nitrogen tube furnace is 2-4°C / min, preferably 4°C / min, the calcination temperature is 500-600°C, preferably 550°C, and the calcination time is 4-6 hours, preferably 4 hours.

[0044] In some embodiments, the present invention provides a carbon nitride nanotube photocatalyst prepared according to the method.

[0045] In some embodiments, the present invention also provides the use of the carbon nitride nanotube photocatalyst in a photocatalytic oxidation copper dissolution reaction. The carbon nitride nanotube photocatalyst provided by the present invention has better visible light response characteristics than the traditional catalyst titanium dioxide (commercial code P25), and can achieve better copper dissolution effect in the photocatalytic copper oxidation reaction.

[0046] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0047] The experimental methods or test methods described in the following examples are conventional methods unless otherwise specified; the raw materials and auxiliary agents are obtained from conventional commercial channels or prepared by conventional methods unless otherwise specified.

[0048] Example 1

[0049] A method for preparing a carbon nitride nanotube photocatalyst, the specific steps are as follows:

[0050] (1) 2.0 g of melamine and 2.0 g of cyanuric acid were placed in 40 mL of dimethyl sulfoxide, and stirred for reaction at room temperature for 2 h. After the reaction, centrifugation, alcohol washing, and drying were performed in sequence to obtain melamine-cyanuric acid spherical supramolecular aggregates;

[0051] (2) placing the obtained spherical supramolecular aggregates in a hydrochloric acid solution with a pH of 2, wherein the ratio of the spherical supramolecular aggregates to the hydrochloric acid solution is 2 g:100 mL, reacting at 80° C. for 6 h, and after the reaction is completed, centrifuging, washing with water, and drying in sequence to obtain a rod-shaped precursor;

[0052] (3) placing the rod-shaped precursor in a cyanamide solution with a concentration of 10 wt %, wherein the ratio of the rod-shaped precursor to the cyanamide solution is 1.5 g:30 mL, stirring the mixture for 2 h at room temperature, and centrifuging and drying the mixture in sequence after the reaction to obtain a supramolecular precursor;

[0053] (4) The supramolecular precursor was transferred to a nitrogen tube furnace and heated to 550 °C at a heating rate of 4 °C / min for 4 h to obtain a carbon nitride nanotube photocatalyst, which was denoted as GCN-T.

[0054] Figure 1 This is the X-ray diffraction pattern of the carbon nitride nanotube photocatalyst prepared in this example. Figure 1 It can be seen that the two significant characteristic peaks at 12.79° and 27.28° are the (100) and (002) crystal planes of GCN-T, corresponding to the planar structure of the heptazine ring and the interlayer stacking of the aromatic system, respectively.

[0055] Figure 2 This is the Fourier transform infrared spectrum of the carbon nitride nanotube photocatalyst prepared in this example. Figure 2 It can be seen that 810cm -1 The absorption peaks at 1200-1750cm are due to the stretching vibration of the heptazine ring structure unit in the main structure of graphite-like carbon nitride. -1 The band at 3000-3500cm-1 is attributed to the stretching vibration of the aromatic heterocycle, confirming the formation of the CN hybrid structure. -1 The characteristic peak at corresponds to the stacking structure of the -NH2 group.

[0056] Figure 3 c is a scanning electron microscope image of the carbon nitride nanotube photocatalyst prepared in this example. Figure 3 c It can be seen that the carbon nitride nanotube photocatalyst synthesized in this example has a hollow tubular structure and good morphology.

[0057] Figure 5 This is the solid UV-visible diffuse reflectance spectrum of the carbon nitride nanotube photocatalyst prepared in this example. Figure 5 It can be seen that the carbon nitride nanotube photocatalyst synthesized in this example has visible light absorption performance.

[0058] Example 2

[0059] The difference from Example 1 is that ethylene glycol is used to replace dimethyl sulfoxide, and the other steps are consistent with Example 1.

[0060] The scanning electron microscope image of the spherical supramolecular aggregates of melamine-cyanuric acid obtained in Example 2 is shown in Figure 4 a.

[0061] Example 3

[0062] The difference from Example 1 is that the obtained spherical supramolecular aggregates are placed in a sulfuric acid solution with a pH of 3, and the remaining steps are consistent with Example 1. The scanning electron microscopy image of the rod-shaped precursor obtained in Example 3 is shown in Figure 4 b.

[0063] Example 4

[0064] The difference from Example 1 is that the rod-shaped precursor is placed in a cyanamide solution with a concentration of 20 wt%, and the other steps are consistent with Example 1. The scanning electron microscope image of the carbon nitride nanotube photocatalyst obtained in Example 4 is shown in FIG. Figure 4 c. From Figure 4 c It can be seen that the carbon nitride nanotube photocatalyst obtained in this example has a hollow tubular structure and a good morphology.

[0065] Comparative Example 1

[0066] The difference from Example 1 is that the rod-shaped precursor is not treated with cyanamide solution, and the other steps are consistent with Example 1. The scanning electron microscope image of the carbon nitride photocatalyst obtained in Comparative Example 1 is shown in Figure 3 d. From Figure 3 d It can be seen that the carbon nitride nanotube photocatalyst obtained in this comparative example presents a tubular morphology structure that is obviously broken and collapsed.

[0067] Comparative Example 2

[0068] The difference from Example 1 is that the supramolecular precursor is placed in a muffle furnace for calcination, and the remaining steps are consistent with Example 1. The scanning electron microscope image of the carbon nitride photocatalyst obtained in Comparative Example 2 is shown in Figure 4 d. From Figure 4 d It can be seen that the carbon nitride nanotube photocatalyst obtained in this comparative example has many structural defects in the tubular morphology.

[0069] Application Example 1

[0070] The carbon nitride nanotube photocatalyst (GCN-T) prepared in Example 1 was used as a photocatalyst to carry out a photocatalytic oxidation copper dissolution reaction, and the specific steps are as follows:

[0071] 20.0 mg of carbon nitride nanotube photocatalyst and 3.0 mg of copper foil were added to a quartz reactor, and then 50 mL of acetonitrile solvent was added. The photocatalytic oxidation copper dissolving reaction was carried out under normal pressure continuous flow conditions in the photocatalytic reaction equipment. Oxygen was introduced into the quartz reactor, and the oxygen inlet flow rate was controlled to be 1 L / min by a flowmeter. The magnetic stirrer was turned on, and a xenon lamp was used as the light source. The photocatalytic reaction temperature was maintained at 10°C using a circulating water cooling system. The photocatalytic reaction was carried out for 8 hours. After the reaction was completed, the copper dissolving reaction liquid was filtered and collected, the absorbance was measured, and the solubility of the copper foil was calculated by the absorbance.

[0072] Figure 6 This is the copper foil dissolution rate curve of the photocatalytic copper oxidation reaction under full spectrum conditions. Figure 6 It can be seen that under full spectrum conditions, after the carbon nitride nanotube photocatalyst prepared in Example 1 photocatalytically oxidized copper-dissolving reaction for 8 hours, the copper foil solubility was 21.05 mg / L, and the copper foil dissolution rate was 35.06%.

[0073] Application Example 2

[0074] The carbon nitride nanotube photocatalyst (GCN-T) prepared in Example 1 and the commercial TiO2 photocatalyst (trade code P25) were used as photocatalysts to carry out photocatalytic oxidation copper dissolution reaction. The specific steps are as follows:

[0075] 20.0 mg of carbon nitride nanotube photocatalyst (or P25) and 3.0 mg of copper foil were added to a quartz reactor, and then 50 mL of acetonitrile solvent was added. The photocatalytic oxidation copper dissolving reaction was carried out under normal pressure continuous flow conditions in the photocatalytic reaction equipment. Oxygen was introduced into the quartz reactor, and the oxygen inlet flow rate was controlled to be 1 L / min by a flowmeter. The magnetic stirrer was turned on, a xenon lamp was used as the light source, and a 400 nm filter was used to intercept ultraviolet light with a wavelength less than 400 nm. The photocatalytic reaction temperature was maintained at 10° C. using a circulating water cooling system, and the photocatalytic reaction was carried out for 8 hours. After the reaction was completed, the copper dissolving reaction liquid was filtered and collected, the absorbance was measured, and the solubility of the copper foil was calculated by the absorbance.

[0076] Figure 7 This is a comparison of the photocatalytic copper oxidation effects of carbon nitride nanotube photocatalysts and commercial TiO2 photocatalysts under visible light conditions. Figure 7It can be seen that under visible light conditions, the carbon nanotube photocatalyst prepared in Example 1 has a copper foil solubility of 8.55 mg / L and a copper foil dissolution rate of 14.24% after 8 hours of photocatalytic oxidation and copper dissolution reaction. The copper foil solubility of the commercial TiO2 photocatalyst (trade code P25) is 0.27 mg / L and the dissolution rate is 0.45%. This shows that the carbon nanotube photocatalyst has better visible light response performance than the traditional TiO2 photocatalyst.

[0077] Application Example 3

[0078] The carbon nitride photocatalysts prepared in Comparative Example 1 and Comparative Example 2 were respectively used as photocatalysts to carry out photocatalytic oxidation copper dissolution reaction, and the specific steps were as follows:

[0079] 20.0 mg of carbon nitride photocatalyst and 3.0 mg of copper foil were added to a quartz reactor, and then 50 mL of acetonitrile solvent was added. The photocatalytic oxidation copper dissolving reaction was carried out under normal pressure continuous flow conditions in the photocatalytic reaction equipment. Oxygen was introduced into the quartz reactor, and the oxygen inlet flow rate was controlled to be 1 L / min by a flowmeter. The magnetic stirrer was turned on, and a xenon lamp was used as the light source (or a xenon lamp was used as the light source, and a 400 nm filter was used to intercept ultraviolet light with a wavelength less than 400 nm). The photocatalytic reaction temperature was maintained at 10° C. using a circulating water cooling system, and the photocatalytic reaction was carried out for 8 hours of irradiation. After the reaction was completed, the copper dissolving reaction solution was filtered and collected, the absorbance was measured, and the solubility of the copper foil was calculated by the absorbance.

[0080] For the carbon nitride photocatalyst prepared in Comparative Example 1, after 8 hours of full-spectrum photocatalytic oxidation copper dissolution reaction, the solubility of copper foil was 2.45 mg / L, and the dissolution rate of copper foil was 4.08%; after 8 hours of visible light photocatalytic oxidation copper dissolution reaction, the solubility of copper foil was 1.12 mg / L, and the dissolution rate of copper foil was 1.87%.

[0081] For the carbon nitride photocatalyst prepared in Comparative Example 2, after 8 hours of full-spectrum photocatalytic oxidation copper dissolution reaction, the solubility of copper foil was 4.49 mg / L, and the dissolution rate of copper foil was 7.49%; after 8 hours of visible light photocatalytic oxidation copper dissolution reaction, the solubility of copper foil was 2.07 mg / L, and the dissolution rate of copper foil was 3.45%.

[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a carbon nitride nanotube photocatalyst, characterized in that: The following steps are involved: (1) placing melamine and cyanuric acid in an organic solvent, stirring and reacting at room temperature, and centrifuging, washing, and drying in sequence after the reaction to obtain melamine-cyanuric acid spherical supramolecular aggregates; (2) placing the obtained spherical supramolecular aggregates in an acidic solution for heating reaction, and after the reaction is completed, centrifuging, washing, and drying in sequence to obtain a rod-shaped precursor; (3) placing the rod-shaped precursor in a cyanamide solution and reacting it at room temperature, and after the reaction is completed, centrifuging and drying are performed in sequence to obtain a supramolecular precursor; (4) calcining the supramolecular precursor at high temperature to obtain carbon nitride nanotube photocatalyst.

2. The method for preparing the carbon nitride nanotube photocatalyst according to claim 1, characterized in that: The mass ratio of melamine to cyanuric acid in step (1) is 1-1.5:1-1.

5.

3. The method for preparing the carbon nitride nanotube photocatalyst according to claim 1, characterized in that: The organic solvent in step (1) is selected from any one of dimethyl sulfoxide and ethylene glycol.

4. The method for preparing the carbon nitride nanotube photocatalyst according to claim 1, characterized in that: In step (2), the pH value of the acidic solution is controlled within the range of 2-3, the heating reaction temperature is 70-80° C., and the heating reaction time is 4-6 hours.

5. The method for preparing the carbon nitride nanotube photocatalyst according to claim 1, characterized in that: The ratio of the spherical supramolecular aggregates to the acidic solution in step (2) is (2-3) g: (100-150) mL.

6. The method for preparing the carbon nitride nanotube photocatalyst according to claim 1, characterized in that: The concentration of the cyanamide solution in step (3) is 5-20%, and the ratio of the rod-shaped precursor to the cyanamide solution is (1-1.5) g: (20-30) mL.

7. The method for preparing the carbon nanotube photocatalyst according to claim 1, characterized in that: The calcination in step (4) is carried out in a nitrogen tube furnace.

8. The method for preparing the carbon nanotube nitride photocatalyst according to claim 7, characterized in that: The heating rate in the nitrogen tube furnace is 2-4°C / min, the calcination temperature is 500-600°C, and the calcination time is 4-6 hours.

9. The carbon nitride nanotube photocatalyst prepared according to the method according to any one of claims 1 to 8.

10. A carbon nitride nanotube photocatalyst prepared by the method according to any one of claims 1 to 8, or use of the carbon nitride nanotube photocatalyst according to claim 9 in a photocatalytic oxidation copper dissolution reaction.